2013
DOI: 10.1210/jc.2012-3982
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Stalk Interruption Syndrome and Isolated Pituitary Hypoplasia May Be Caused by Mutations in Holoprosencephaly-Related Genes

Abstract: The data suggest that HPE-related gene mutations are implicated in the etiology of isolated pituitary defects (PSIS or IPH). Alternatively, PSIS or IPH may constitute mild forms of an expanded HPE spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 37 publications
0
62
0
4
Order By: Relevance
“…Deletions or mutations of this gene, which affect NODAL signaling pathway of the neural axis development, can result in holoprosencephaly. Its microforms can range from pituitary abnormality to single central incisor [Gripp et al, 2000;Tatsi et al, 2013;Gondré-Lewis et al, 2015]. Our patient did not have holoprosencephaly, which suggests incomplete penetrance [Hasi-Zogaj et al, 2015].…”
Section: Discussionmentioning
confidence: 53%
“…Deletions or mutations of this gene, which affect NODAL signaling pathway of the neural axis development, can result in holoprosencephaly. Its microforms can range from pituitary abnormality to single central incisor [Gripp et al, 2000;Tatsi et al, 2013;Gondré-Lewis et al, 2015]. Our patient did not have holoprosencephaly, which suggests incomplete penetrance [Hasi-Zogaj et al, 2015].…”
Section: Discussionmentioning
confidence: 53%
“…HPE and its microforms have been observed in approximately 12% of these patients [8]. Interestingly, HPE has been linked to GH deficiency and there is evidence that isolated pituitary hypoplasia and pituitary stalk interruption syndrome are milder forms of HPE [6, 9]. Reports have varied on the developmental and behavioral manifestations, although recent reviews estimate an average IQ of 69, with patients ranging from mild impairment to normal functioning [2].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the importance of BMP and FGF pathways to formation of the Rathke's pouch precursors in the essential hypothalamus-pouch connection during pituitary development, and the sonic hedgehog, a ligand of the hedgehog family (SHH), Wnt/beta-catenin and notch pathways to commitment/differentiation of those precursors [reviewed in [2,44]]. In this context, a heterozygous SHH mutation had recently been found in a human female patient with combined pituitary hormone deficiency among other alterations [72]. …”
Section: From Adult Stem To Committed and Differentiated Cells In The Apmentioning
confidence: 99%